Black Swan Event and The Stock Market Volatility Response to Shocks in Developed, Emerging, Frontier and the BRIC Markets: Lessons from the COVID-19 Pandemic - Nayanjyoti Bhattacharjee; Anupam De (BBR: Brazilian Business Review)
We study the impact of shocks (news flow) on stock market volatility in different economic regions, namely the developed, emerging, frontier, and BRIC stock markets during the COVID-19 pandemic, which was a‘Black Swan Event’. The daily returns of relevant MSCI indices from January 30, 2020 to October 30, 2020 are examined using the EGARCH model’s News Impact Curve to gain a perspective on the volatility behaviour in stock markets in the developed, emerging, frontier, and BRIC countries' stock markets. Evidence suggests that the developed markets in the Pacific and Europe, the BRIC countries, the emerging markets in Asia, Europe, and Latin America and the frontier markets in Asia were associated with asymmetric volatility response to shocks. Further, the developed markets in North America, and the frontier markets in Africa were associated with a symmetric volatility response. We observe that the volatility response to shocks in different regions is not uniform and varies according to the size and sign of the shock. The findings of the study provide insights to the investors and the academics in understanding the behaviour of volatility globally during a Black Swan Event, and provides critical inputs in global portfolio decisions.